2022
DOI: 10.1111/pbi.13927
|View full text |Cite
|
Sign up to set email alerts
|

A teosinte‐derived allele of an HKT1 family sodium transporter improves salt tolerance in maize

Abstract: The sodium cation (Na + ) is the predominant cation with deleterious effects on crops in saltaffected agricultural areas. Salt tolerance of crop can be improved by increasing shoot Na + exclusion. Therefore, it is crucial to identify and use genetic variants of various crops that promote shoot Na + exclusion. Here, we show that a HKT1 family gene ZmNC3 (Zea mays L. Na + Content 3; designated ZmHKT1;2) confers natural variability in shoot-Na + accumulation and salt tolerance in maize. ZmHKT1;2 encodes a Na + -p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Subfamily I HKT members (HKT1), encoded by AtHKT1 from Arabidopsis, OsHKT1;4 and OsHKT1;5 from rice, and GmHKT1;1 from soybean, reduce the transport of Na + from root to shoot by retrieving Na + from the root xylem (Uozumi et al, 2000; Ren et al, 2005; Oda et al, 2018). Similar mechanisms have been reported in wheat for the TmHKT1;4 and TmHKT1;5 genes (Huang et al, 2006; Munns et al, 2012; Byrt et al, 2014) and in maize for ZmHKT1;1 and ZmHKT1;2 (Zhang et al, 2018, 2023b). The Na + permeability of AtHKT1 is inhibited by PP2C49 (a clade G–type PP2C) under salt stress.…”
Section: Physiological and Molecular Underpinnings Of Plant Responses...supporting
confidence: 82%
See 2 more Smart Citations
“…Subfamily I HKT members (HKT1), encoded by AtHKT1 from Arabidopsis, OsHKT1;4 and OsHKT1;5 from rice, and GmHKT1;1 from soybean, reduce the transport of Na + from root to shoot by retrieving Na + from the root xylem (Uozumi et al, 2000; Ren et al, 2005; Oda et al, 2018). Similar mechanisms have been reported in wheat for the TmHKT1;4 and TmHKT1;5 genes (Huang et al, 2006; Munns et al, 2012; Byrt et al, 2014) and in maize for ZmHKT1;1 and ZmHKT1;2 (Zhang et al, 2018, 2023b). The Na + permeability of AtHKT1 is inhibited by PP2C49 (a clade G–type PP2C) under salt stress.…”
Section: Physiological and Molecular Underpinnings Of Plant Responses...supporting
confidence: 82%
“…In Chang7-2, an LRT/Gypsy retrotransposon insertion truncates ZmHKT1;1, leading to increased leaf Na + content and a salt-hypersensitive phenotype (Zhang et al, 2018). In addition, a GWAS revealed that another HKT1 family Na + transporter gene known as ZmNC3/ZmHKT1;2 and a HAK family Na + transporter gene ZmNC2/ZmHAK4 are associated with the shoot Na + content of salt-grown maize seedlings (Zhang et al, 2019a(Zhang et al, , 2023b. A naturally occurring non-synonymous SNP (SNP947-G) increases the Na + transport activity of ZmHKT1;2 by approximately two-fold, thereby promoting shoot Na + exclusion and salt tolerance.…”
Section: Natural Variations Associated With Rice Salt Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…One of the main bottlenecks in breeding programs is the strong reduction of phenotypic and genetic diversity in modern germplasms, due to domestication itself firstly and the development of commercial cultivars secondly, which has led to the phenomenon of genetic erosion, as recently remarked by Kromdijk and McCormick (2022) . In fact, the selection of genes related to agronomic traits during the domestication process ( Liang et al ., 2021 ) was accompanied by the loss of alleles involved in abiotic stress tolerance ( Zhang et al ., 2023 ). Therefore, the identification and introduction of genetic determinants that were lost during domestication may facilitate the development of salt-tolerant crops ( Eckardt et al ., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in a model plant Arabidopsis thaliana and its mutants have uncovered the regulated mechanisms of salt tolerance, including the salinity overly sensitive (SOS) signaling pathway, the calcium signaling pathway, mitogen-activated protein kinase cascades, and reactive oxygen species (ROS) homeostasis [ 11 , 12 ]. In crop plants, many salt-responsive proteins have been reported, such as vacuolar Na + /H + antiporters (NHXs), high-affinity K + transporters (HKTs), and SOSs, which have important roles in the regulation of Na + and K + ion balance [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%